2014
DOI: 10.1002/art.38886
|View full text |Cite
|
Sign up to set email alerts
|

Intraarticular Hip Injection and Early Revision Surgery Following Total Hip Arthroplasty: A Retrospective Cohort Study

Abstract: Objective. Therapeutic intraarticular injections are used in the management of hip osteoarthritis (OA).Some studies suggest that their use increases the risk of infection and subsequent revision surgery after primary total hip arthroplasty (THA), while others do not. We undertook this study to clarify the relationship between prior intraarticular injection and the risk of complication in a subsequent primary THA.Methods. In a cohort of patients with hip OA who underwent a primary elective THA between 2002 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 25 publications
(29 reference statements)
0
23
0
Order By: Relevance
“…While matched cohorts were used in a few studies, multivariableadjusted data were not reported by majority studies, prohibiting a pooled analysis. In the few studies reporting multivariableadjusted results, some demonstrated no increased risk of PJI (19,31) while others demonstrated an increased risk (21,34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While matched cohorts were used in a few studies, multivariableadjusted data were not reported by majority studies, prohibiting a pooled analysis. In the few studies reporting multivariableadjusted results, some demonstrated no increased risk of PJI (19,31) while others demonstrated an increased risk (21,34).…”
Section: Discussionmentioning
confidence: 99%
“…Seven studies were excluded with reasons. Finally, 19 studies were included in this systematic review and meta-analysis (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36).…”
Section: Search and Study Detailsmentioning
confidence: 99%
“…Patients who had an injection within 1 year of THA showed higher PJI rates than patients who did not receive prior intra-articular injection (3.3% vs 2.4%, P ¼ .04). Also, controlling for confounders, an elevated hazard ratio of 1.37 of PJI was found after prior injection [25]. Additionally, McIntosh et al found no difference in infection rate in a matched cohort of 448 (224 per group) THAs.…”
Section: Discussionmentioning
confidence: 96%
“…Of the 2 studies reporting increased infection rates, Kaspar et al [8] showed PJI rates of 10% (4/40 patients) in their CS group, compared to 0% in the control group (0/40 patients), but their study lacked statistical power. Second, Ravi et al [25] included 37,881 THA patients in their database study, of whom 2468 received an intra-articular injection within 5 years prior to THA (69% <1 year). Patients who had an injection within 1 year of THA showed higher PJI rates than patients who did not receive prior intra-articular injection (3.3% vs 2.4%, P ¼ .04).…”
Section: Discussionmentioning
confidence: 99%
“…Cortisone administered in and around the joint prior to arthroplasty may also subject the patient to a slightly elevated risk of deep prosthetic infection. 10,11 This risk is considered so significant that the American Academy of Orthopaedic Surgeons categorizes IA cortisone injection as a time-dependent risk factor for prosthetic joint infection. 12 Although controversy remains, most surgeons have settled on waiting a minimum of 3 months after corticosteroid injection before prosthetic implantation.…”
Section: See Related Article On Page 1452mentioning
confidence: 99%